PERTUMBUHAN DAN PRODUKSI LEGUMINOSA PADA PEMOTONGAN KEDUA YANG DIPUPUK DENGAN BIO SLURRY - Witariadi N.M.; Candraasih K. (Udayana University, 2018)
This study aims at determine the growth and production of legume on the second regrowth fertilized with bio slurry. The study was conducted by using a completely Randomized Design (CRD) with two factors. Legume plants are Centrocema pubescens and Clitoria ternatea are the first factor, and the second factor are dosage of bioslurry fertilizer: 10 tons / ha of bio slurry; 20 tons/ha of bio slurry; and 30 tons/ ha of bio slurry. Variables observed were: plant height, number of branches, number of leaves, leaf area, leaf dry weight, dry weight of stem, leaf stem ratio, and total dry weight of forage. The results showed that there was interaction between fertilizer dosage and legume plant species on variables: number of branches, number of leaves, leaf dry weight, total dry weight of production, and leaf stem ratio. Interaction shows that the growth and production of forage legumes can be influenced by both bio slurry fertilizer and legume species either jointly or individually. Increasing of bio slurry dosage can increase growth and production of legume. It can be concluded that the best results were obtained on Clitoria ternatea with 30 tons/ha dosage of bio slurry. Keywords: growth, production, leguminous, bio slurry